Measuring Biological Impacts of Nanomaterials - Wegener, Joachim; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book reviews several aspects of the biological response to nanoscale particles on a molecular and cellular level. Nanoscale materials and nanoscale particles in particular have interesting properties and beneficial applications. While they thus have entered our daily lifes on many different levels (from electronics, over textiles, packaging or surface modifications, to biomedical applications), general rules describing their interaction with biological structures and biological matter are still difficult to derive. The existing literature suggests a variety of interaction schemes between nanoparticles and biological objects, not dispelling the public concerns about possible health effects and harmful properties. A systematic approach to the problem is needed and timely. This book specifically emphasizes bioanalytical problems starting from the characterization of the nanomaterials to the pitfalls and potential artifacts of state-of-the-art cytotoxicityassays that are frequently used to study harmful effects on cells. It also highlights the application of label-free bioanalytical techniques that can potentially complement the present approaches and hence provide new perspectives on this highly discussed cutting-edge field of research and public concern.
Standardized Physical Characterization of Nanoscale Particles: Towards a Bar Code for Nanomaterials -- Bioanalytical Aspects for the detection of nanoparticle effects on cells -- Interactions of Nanoscale Particles with the Air-Water Interface: Implications for Lung Effects of Nanomaterials -- Carbon Dots: Synthesis, Characterization and Bioanalytical Applications -- Changes in Motility of Cultured Cells caused by Nanoparticle Encounter -- Cellular Response to Nano- and Mesoscale Particles probed by Label-free Detection Techniques.
Keywords: Analytical chemistry; Nanochemistry; Biochemistry; Medicine -- Research; Biology -- Research; Biophysics; Biotechnology; Analytical Chemistry; Nanochemistry; Biochemistry; Biomedical Research; Biophysics; Biotechnology